HYGIENIC EVALUATION OF EXPOSURE DOSES FOR THE VORONEZH REGION POPULATION FROM THE NATURAL AND TECHNOGENOUSLY MODIFIED BACKGROUND - Yu. I. Stepkin; M. K. Kuzmichev; O. V. Klepikov; E. М. Studenikina (Радиационная гигиена)
The purpose of the study was to estimate the doses to the Voronezh region population from natural sources of ionizing radiation and the technologically altered background in the territory of Voronezh Region. The data of forms of state statistical observation No. 4-DOZ “Information on the doses of population exposure due to natural and technologically altered background” for 20102017 and the radiation and hygienic passport of the territory of the Voronezh Region were used. The average annual per caput effective dose due to all types of ionizing radiation remains stable with a slight upward trend and lies in the range from 2.925 (2010) to 3.656 mSv (2017). Natural sources are the main dose-forming factors for the population. Their annual contribution to the annual effective dose ranges from 74.96 to 83.65%. The leading contribution to the total dose from natural sources is the exposure due to the inhalation of radon isotopes: it ranges from 37.6 to 51.1%. In second place,there is the share of external exposure from sources of terrigenous origin, which ranges from 21.2 to 28.9% of the total dose. The average annual effective dose of natural exposure to humans varies from 2,355 to 2,980 mSv / year, the exposure from radon – from 0,83 to 1,65 mSv / year. The dose from technogenic-altered radiation background, including global radioactive fallout due to atmospheric nuclear tests and due to past radiation accidents are insignificant (0,062 mSv / year). Its annual contribution to the total dose is less than 2%. Based on the results of the assessment of the indicators characterizing the level of exposure of sources of ionizing radiation to natural and technogenic-altered radiation background, no excess of radiation safety standards has been recorded. The situation associated with exposure to ionizing radiation sources in the Voronezh region has been described as safe for the last 8 years.